2015
DOI: 10.3390/w7073431
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Water Parallel Pricing System against Drought in China: A Study Based on a CGE Model with Multi-Provincial Irrigation Water

Abstract: The reform of water management in China is still in progress, and the pricing of water resources is undertaken in parallel, with a divide between irrigation water and pipe water associated with different users: The supply of irrigation water is regulated by local government and that of pipe water is operated by the production sector of pipe water. Based on a literature review and an interview survey of farmers, this study incorporated the water parallel pricing system of China within a computable general equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…To acquire a basic understanding of irrigation water pricing and management, the authors conducted a field survey in rural areas of Jilin and Anhui provinces [14,26]. In the first stage of the modeling process, 15 provinces were selected for an in-depth exploration of the effects of water-saving policy on agricultural production and local rural households.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To acquire a basic understanding of irrigation water pricing and management, the authors conducted a field survey in rural areas of Jilin and Anhui provinces [14,26]. In the first stage of the modeling process, 15 provinces were selected for an in-depth exploration of the effects of water-saving policy on agricultural production and local rural households.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely accepted that if water users pay the marginal costs of water supply, significant advances can be made toward increasing water-management efficiency [25]. However, irrigation water prices in China are already heavily subsidized and prices paid by farmers are insufficient to recover water supply costs [26,27]. Under current subsidy conditions, farmers have no incentive to save water by improving irrigation efficiency [28,29].…”
Section: Context To Water Pricing Reformmentioning
confidence: 99%
“…Moreover, the substitution elasticity among different factors and commodities, and the income elasticity of rural and urban households, were obtained from Ge et al [19] and Zhong et al [36], as shown in Table 2. The dynamic model is run up to the year 2025 from the base year of 2010.…”
Section: Data and Model Calibrationmentioning
confidence: 99%
“…Droughts are recognized as an environmental disaster, the consequence of a reduction in precipitation over an extended period of time [1], negatively affecting agriculture, domestic water supply and economic growth [2], and in some cases even altering the functioning of natural ecosystems [3]. Droughts are especially important in regions where economic activities are highly dependent on water resources [4], such as in mountain regions which traditionally provide water resources and services to local communities and lowland residents [5].…”
Section: Introductionmentioning
confidence: 99%